Zhuangzi and collaboration in animals: a critical conceptual analysis of shared intentionality - Papadopoulos, Dennis (Frontiers in Psychology, 2023)
Shared intentionality is a specific form of shared agency where a group can be understood to have an intention. It has been conjectured that humans are better equipped for collaboration than other animals because humans but not other great apes share intentions. However, exporting shared intentionality from a debate about the ontology of mental state attributions like intentions to groups does not seamlessly lend itself to evolutionary science. To explore and de-center the implicit assumptions of Western conceptions of cooperation, I look at Zhuangzi’s philosophy of (in)action. This philosophy treats the actions of individuals as always a form of co-action alongside other agencies to whom one must adapt. Thinking of collaboration as a product of skillful co-action, not shared intention, sidesteps asking about cooperation in “kinds” or levels. Instead, it directs attention to the know-how and behavioral flexibility needed to make our constant coordination adaptive.